2020
DOI: 10.1002/eat.23267
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repetitive transcranial magnetic stimulation on food choice‐related self‐control in patients with severe, enduring anorexia nervosa

Abstract: ObjectiveIndividuals with anorexia nervosa (AN) pursue low‐fat, low‐calorie diets even when in a state of emaciation. These maladaptive food choices may involve fronto‐limbic circuitry associated with cognitive control, habit, and reward. We assessed whether high‐frequency repetitive transcranial magnetic stimulation (rTMS) to the left dorsolateral prefrontal cortex (DLPFC) influenced food‐related choice behavior in patients with severe, enduring (SE)‐AN.MethodThirty‐four females with SE‐AN completed a Food Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…Examination of actual food choices, and the influence of individualized food valuation ratings on food choice, may help clarify similarities and differences in components of decision‐making between the subtypes of AN. In the present study, we used a Food Choice Task previously shown to capture restrictive food choice in individuals with AN (Dalton et al, 2020; Foerde, Steinglass, Shohamy, & Walsh, 2015; Steinglass, Foerde, Kostro, Shohamy, & Walsh, 2015) and relate to actual food intake the following day to examine whether food‐based decision‐making differs between AN subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of actual food choices, and the influence of individualized food valuation ratings on food choice, may help clarify similarities and differences in components of decision‐making between the subtypes of AN. In the present study, we used a Food Choice Task previously shown to capture restrictive food choice in individuals with AN (Dalton et al, 2020; Foerde, Steinglass, Shohamy, & Walsh, 2015; Steinglass, Foerde, Kostro, Shohamy, & Walsh, 2015) and relate to actual food intake the following day to examine whether food‐based decision‐making differs between AN subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that a higher number of rTMS sessions give better clinical results [26,27]. An ancillary analysis of the sample of a randomized controlled feasibility trial on rTMS [26], using a food choice task, found a decrease in self-controlled food choices, suggesting than rTMS may promote more flexibility in relation to food choices [28]. Finally, the feasibility and safety of rTMS of DLPFC in patients with AN have been confirmed by these randomized controlled trials [25][26][27].…”
Section: Anorexia Nervosamentioning
confidence: 83%
“…Stimulation of deeper areas using an H coil might be more effective, leading to enduring benefits. With the exception of Dalton et al [28,44], the randomized controlled studies only proposed a limited number of pulses and 1 to 10 sessions (i.e., about 10,000 pulses maximum). It is likely that more sessions are needed to modify neural programs and their associated behaviors.…”
Section: Current Evidence and Issuesmentioning
confidence: 99%
“…Analyses were rerun with the (76-item) subset of foods that has been used as part of the Food Choice Task in multiple existing studies with eating disorder populations (e.g., Foerde et al, 2015;Dalton et al, 2020). Differences between low-fat and high-fat foods were more pronounced in analyses with the 76-item subset; however, outcomes did not qualitatively differ from those of the primary analysis, and are presented in the Supplementary Information (Part 2) and Supplementary Tables (File 2).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…The consistency of items across stimulus set and laboratory meal better enables assessment of whether tasks involving the image set predict actual eating behavior (e.g., Foerde et al, 2015Foerde et al, , 2020. The food images have been used in tasks designed to capture the persistent selection of low-fat food items across eating disorders in the United States (e.g., Foerde et al, 2015Foerde et al, , 2020Gianini et al, 2019) and United Kingdom (e.g., Steinglass et al, 2015;Dalton et al, 2020). The same images have been used to study cognitive mechanisms involved in food-choice decision-making that may differentiate individuals with anorexia nervosa from healthy individuals (Bakkour et al, 2018).…”
Section: Introductionmentioning
confidence: 99%